Indirect Tensile Test (IDT) to Determine Asphalt Mixture Performance Indicators during Quality Control Testing in New Jersey. Issue 28 (December 2018) - Bennert, Thomas; Haas, Edwin; Wass, Edward
In recent years, there has been a growing interest in incorporating performance testing during the mixture design and quality control testing of asphalt mixtures. The move toward utilizing performance related specifications (PRS) and balanced mixture design concepts have pushed the need for asphalt mixture performance testing to the forefront. Numerous researchers have proposed a variety of laboratory tests that have showed promise at predicting asphalt mixture performance, yet most of these test methods are never adopted due to a number of issues often cited by the asphalt industry: (1) equipment cost; (2) equipment/test method complexity; and (3) time/labor effort required. The research presented here summarizes the effort to evaluate the indirect tensile test (IDT) as a potential performance indicator for hot-mix asphalt that can be easily utilized during quality control testing at an asphalt plant. Utilizing the same test equipment and basic procedure, both high-temperature rutting and intermediate-temperature fatigue cracking can be evaluated in a timely manner. Comparison testing to more standardized and accepted rutting and fatigue cracking test methods have shown excellent agreement, indicating that the suite of IDT tests have potential for adoption within a quality control testing program. Examples of criteria are given utilizing the New Jersey Department of Transportation's (NJDOT) PRS.